PROBLEMS OF SPEECH ETIQUETTE FORMATION IN PRESCHOOL CHILDREN (Scientific journal of the Fergana State University, 2023)
From birth, a person enters into relationships with other people. Without communication, his psyche is not formed. In the process of communication, the child learns about the world around him, himself, learns the language, the norms of relations between adults and peers. needTeaching the basics of speech behavior and manners is effective from preschool age - from the age of mastering the norms of language, knowledge, and verbal politeness. targeted works are being carried out.At the same time, education of the manners of speech behavior in preschool childhood is considered not only to improve the child's speech as a means of communication, but also to teach children clear, understandable ways of showing respect to the person.